2013
DOI: 10.1016/j.canlet.2012.08.030
|View full text |Cite
|
Sign up to set email alerts
|

Pregnane xenobiotic receptor in cancer pathogenesis and therapeutic response

Abstract: Pregnane xenobiotic receptor (PXR) is an orphan nuclear receptor that regulates the metabolism of endobiotics and xenobiotics. PXR is promiscuous and unique in that it is activated by a diverse group of xenochemicals, including therapeutic anticancer drugs and naturally-occurring endocrine disruptors. PXR has been predominantly studied to understand its regulatory role in xenobiotic clearance in liver and intestine via induction of drug metabolizing enzymes and drug transporters. PXR, however, is widely expres… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
66
0
1

Year Published

2013
2013
2021
2021

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 72 publications
(70 citation statements)
references
References 153 publications
3
66
0
1
Order By: Relevance
“…In colon cancer cells, expression of wild-type p53 induces apoptosis (Shaw et al, 1992), whereas activation of PXR induces colon tumor growth and malignancy (Wang et al, 2011;Mani et al, 2013;Pondugula and Mani, 2013). In this study, we showed that in colon cancer cell line HCT116, wildtype p53 downregulates PXR activity.…”
Section: Discussionmentioning
confidence: 57%
“…In colon cancer cells, expression of wild-type p53 induces apoptosis (Shaw et al, 1992), whereas activation of PXR induces colon tumor growth and malignancy (Wang et al, 2011;Mani et al, 2013;Pondugula and Mani, 2013). In this study, we showed that in colon cancer cell line HCT116, wildtype p53 downregulates PXR activity.…”
Section: Discussionmentioning
confidence: 57%
“…Highly expressed in the liver and intestinal epithelium, the PXR has been previously characterized as a master regulator of xenobiotic metabolism and clearance (Watkins et al, 2002;Staudinger et al, 2006;Shukla et al, 2011;Dou et al, 2013;Pondugula and Mani, 2013). Acting as a sensor of exogenous chemicals, the PXR's activation leads to the expression of a variety of target genes related to detoxification and efflux pathways.…”
Section: Discussionmentioning
confidence: 99%
“…Threonine-290 Regulates Human PXR Nuclear Translocation Discussion PXR, a member of the nuclear receptor superfamily, was originally characterized as a xenobiotic-activated transcription factor that plays a key role in regulating the expression of genes encoding drugmetabolizing enzymes and drug transporters. It was subsequently found to potentiate various biologic effects associated with pharmacologic and toxicologic consequences-not only the metabolism and clearance of endobiotics and xenobiotics, including various therapeutic drugs and environmental endocrine disruptors, but also cancer pathogenesis (Timsit and Negishi, 2007;Staudinger and Lichti, 2008;Ihunnah et al, 2011;Pondugula and Mani, 2013) and hepatic energy metabolism including gluconeogenesis, the b-oxidation of fatty acids, and lipogenesis (Konno et al, 2008). PXR is activated by the binding of endogenous and exogenous xenobiotics to its ligand-binding domain and is then translocated to the nucleus in which it activates transcription by binding to the xenobiotic-response element in the promoter region of the target gene with RXR (Timsit and Negishi, 2007).…”
Section: Threonine-290 Regulates Human Pxr Nuclear Translocationmentioning
confidence: 99%